2019
DOI: 10.1002/ptr.6527
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina extract enriched for Braun‐type lipoprotein (Immulina®) for inhibition of 4T1 breast tumors' growth and metastasis

Abstract: Spirulina platensis extracts have exhibited considerable anti-cancer effects. To investigate the efficacy of the Spirulina extract enriched for Braun-type lipoprotein (Immulina®) for breast cancer treatment, 4T1 breast tumor-bearing mice were treated with 40 mg/kg Immulina® daily and the tumors' growth and metastasis were assessed. Also, CD4, CD8, and CD56 staining were performed to investigate the Immulina® effect on the immune cells' recruitment to the tumors by immunohistochemistry. Immulina® could signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Apoptosis rate was determined by the apoptosis detection kit (BD Biosciences, USA) according to previous study 52 . 4T1 cells were seeded in 6-well culture plates at a concentration of 1 × 10 5 and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis rate was determined by the apoptosis detection kit (BD Biosciences, USA) according to previous study 52 . 4T1 cells were seeded in 6-well culture plates at a concentration of 1 × 10 5 and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…High delivery efficiency, prolonged drug release, and low systemic toxicity are effective weapons for drug delivery systems to win the battle against metastatic breast cancer. It is demonstrated that Spirulina can be used as a natural carrier to build a drug-loaded system for targeted delivery and fluorescence imaging-guided chemotherapy on breast cancer lung metastases [ 92 ]. The Spirulina’s protein C-phycocyanin (C-PC) inhibited cell proliferation and reduced the colony formation ability of MDA-MB-231 cells.…”
Section: Applications In Oncologymentioning
confidence: 99%
“…Also, CD4, CD8, and CD56 staining were performed to investigate the effect on the immune cells’ recruitment to the tumors by immunohistochemistry. This treatment combination could significantly inhibit 4T1 breast tumors’ growth, decreasing the tumors’ volume compared to the control and the metastatic burden [ 92 ].…”
Section: Applications In Oncologymentioning
confidence: 99%
“…Some of its derivatives are commercially in use as dietary supplements. For example, the company ChromaDex produces an extract called Immulina [ 135 , 136 , 137 ], with some action against IAV thanks to its Braun-type lipoproteins. These lipoproteins activate toll-like receptors, and consequently the immunity system [ 137 ].…”
Section: An Overview Of the Antiviral Effects Of A Supplementary Microalgae Diet And Its Possible Action On Sars-cov-2mentioning
confidence: 99%
“…Immurella, a mix of extracted polysaccharides from Chlorella, had interesting effects when supplemented into the diets of broilers [ 48 , 137 , 152 , 164 ].…”
Section: An Overview Of the Antiviral Effects Of A Supplementary Microalgae Diet And Its Possible Action On Sars-cov-2mentioning
confidence: 99%